Pendidikan dan Pelatihan Pegawai: Tantangan, Strategi dan Implementasi yang Efektif - Rani Maisari; Wahib Assyahri (Jurnal Ilmu Sosial dan Humaniora, 2024)
Employee education and training plays an important role in enhancing employees' knowledge, skills and motivation to improve their performance at work. However, in implementing education and training programmes, organisations are often faced with various challenges that can affect their effectiveness. These challenges include low employee accountability and discipline, lack of work motivation, difficulty in identifying training needs, limited resources, and diverse employee characteristics and participation. This study aims to analyse the factors that influence the success of employee education and training programmes and provide suggestions to overcome the challenges faced. The research method used is a literature study, by analysing various relevant references from leading experts and researchers in the field of education and human resource development. The results show that identification of training needs, programme planning, programme implementation, evaluation and feedback are important steps in managing employee education and training programmes. Factors such as relevance of training materials, quality of instructors and materials, effective evaluation, career development opportunities, and organisational support also play a role in improving the effectiveness of the programme.